Evaluasi Pelaksanaan Rekam Medis Elektronik (RME) Pada Pasien Rawat Jalan Di Puskesmas X - Yaya Aditiya; Dwi Nur Siti Marchamah; Restu Ayu Eka Pustika Dewi (Indonesian Journal of Health Community, 2025)
The provision of medical record files must be able to support health services, especially quality outpatient services. Electronic medical records are a solution to make the provision of medical records in outpatient care fast, easy, and accurate. The purpose to analyze the provision of outpatient medical records based on standard operating procedures. This type of research is descriptive qualitative. Data collection techniques were conducted by conducting interviews and observations. The results of the study are that the provision of outpatient medical record services at Community Health Center X applies electronic medical records and is carried out in accordance with established standard operating procedures.